Mingle Model for Increasing Productive Language Skills and Relationship with Student’s Personality Based on Jung Theory - Suci Ramadhanti Febriani; Wildana Wargadinata; Syuhadak Syuhadak (Ta'lim al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab & Kebahasaaraban, 2021)
This study aims to find the effect of the implemetation of the Mingle Model on productive language skills and the relationship to the personality based on Carl Gustav Jung Theory in Arabic learning at MTsN Batu City, East Java. This research used a quantitative approach by combining the experimental and correlation methods, it was applying the Mingle Model to improve students' productive skills (speaking and writing) which have been divided into two groups; the Experiment and Control group and connected using the correlation method to extroverted and introverted students based on the theory of Carl Gustav Jung. Data collection through questionnaires, tests, and documentation. The results showed that there was a significant relationship to students' productive skills after applying the Mingle Model and there were no significant differences between extroverted and introverted students. This research recommend that the Mingle Model can be applied to improve students' productive skills. This study recommends further research to utilise more varied research methods with more diverse variables.